1999
DOI: 10.1021/jo981478c
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Coriolin

Abstract: An efficient synthetic method for (-)-coriolin has been developed on the basis of a [3+2] cycloaddition reaction of a 1-(methylthio)-2-siloxyallyl cationic species and vinylsulfides. An enantiomerically pure C-ring unit was prepared through optical resolution of five-membered allyl ester 6b using a lipase. The first [3+2] cycloaddition reaction of C-ring unit (S)-7 gave bicyclic ketones 8 and 9, which were easily converted into vinyl sulfide 11. Stereoselective construction of the A-ring was achieved by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…13,14 As shown in Scheme 4, the ABC triquinane ring system of coriolin was constructed via two successive (3+2)-cycloaddition reactions. Treatment of benzyl ether 16 with vinyl sulfide 6 in the presence of EtAlCl 2 provided a 1:1 mixture of annulated products 17 and 18 in diastereomerically pure forms.…”
Section: Heteroatom-substituted Oxyallyl Cationsmentioning
confidence: 99%
“…13,14 As shown in Scheme 4, the ABC triquinane ring system of coriolin was constructed via two successive (3+2)-cycloaddition reactions. Treatment of benzyl ether 16 with vinyl sulfide 6 in the presence of EtAlCl 2 provided a 1:1 mixture of annulated products 17 and 18 in diastereomerically pure forms.…”
Section: Heteroatom-substituted Oxyallyl Cationsmentioning
confidence: 99%
“…[19] After considerable experimentation, we found that exposure of 17 to hydrogen in the presence of palladium on carbon in hexane gave 7 exclusively (95 %i solated yield), [20] while hydrogenation with Crabtreesc atalyst in CH 2 Cl 2 afforded as eparable 1.7:1 mixture of 22-epi-7 and 7,favoring the former isomer. Although 22-epi-7,w hich we set as ap recursor to 2,c ould also be secured (20 %yield through 2steps from 8)byconducting the dithioacetalization at room temperature,w es ought ab etter way to give 22-epi-7 preferentially and examined the stereoselectivity of the hydrogenation of trisubstituted cyclopentene 17 prepared from 8 via thioenol ether 16.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[5] Vinyl sulfides are popular fragments utilized to prepare ketones, [6] olefins, [7] diaryl sulfides, [8] cyclobutyl sulfides, [9] and cyclopentyl sulfides. [10] Alkyl sulfides are generally used as sulfoxide precursors. [11] Sulfide derivatives are also widely used as organic materials in polymer [12] and molecular electronics.…”
Section: Introductionmentioning
confidence: 99%